Repaving the Road of Good Intentions: LGBT Health Care and the Queer Bioethical Lens - Wahlert, Lance (The Hastings Center report, 2014)
As the saying goes, “The road to hell is paved with good intentions.” And in the recent burst of clinical attention being paid to the needs of lesbian, gay, bisexual, and transgender patients, good intentions abound. But while this long-overdue interest in LGBT health care aims to highlight important gaps and bring into relief serious issues in health care delivery for LGBT persons, such work can inadvertently reinforce both the marginalization of sexual minorities and the cultural norms related to sexuality, gender identity, and the conventional family. To ensure that positive outcomes for LGBT patients are inextricably paired with those noble intentions, we advocate for a new, queer bioethics—a methodology of scholastic, bioethical, and critical scrutiny that not only addresses the needs of LGBT persons in health care settings but also considers the perspectives, histories, and feelings of such parties.